Minimum polyethylene glycol 6000 concentration for selecting Musa spp. in vitro plants tolerant to water stress - Leonardo J Moreno-Bermúdez; Maritza Reyes; Rafael Gómez-Kosky; Borys Chong-Pérez (Biotecnología Vegetal, 2017)
Increasingly intense droughts are an abiotic factor which has affected bananas and plantains (Musa spp.) production, therefore it is necessary to obtain tolerant genotypes. Plants in vitro selection offers advantages over field selection as it saves time, resources and permit to work with larger plant volumes. Before to establish an in vitro selection protocol for drought, it is necessary first, to establish some conditions. The aim of this work was to determine the minimum polyethylene glycol 6000 concentration which morpho-physiological variables are affected in in vitro Musa spp. plants, 'Grande naine' (AAA) and 'Pelipita' (ABB) cultivars. In vitro plants were subjected to four polyethylene glycol 6000 concentrations (3, 5, 7 and 9%; w/v) in semisolid multiplication culture medium. Also it was taken into account a control treatment without polyethylene glycol 6000. As stress indicators, plant height, leaf area, fresh weight, dry weight and malondialdehyde content were evaluated. After 30 days of culture, all variables were significantly affected in 'Grande naine' cultivar from 3% polyethylene glycol 6000, whereas in 'Pelipita' cultivar the affections began to be significative from 5%. These results indicated that 'Pelipita' cultivar tolerated the stress better than 'Grande naine'. From this, using these two cultivars as reference standards, the minimum polyethylene glycol 6000 concentration to select in vitro Musa spp. plants, tolerant to water deficit, may be 3%.